2021
DOI: 10.1177/07334648211012530
|View full text |Cite
|
Sign up to set email alerts
|

Voices of Experience: What Do Low-Income Older Adults Tell Us About Mobility, Technology, and Social Participation?

Abstract: Mobility and technology can facilitate in-person and virtual social participation to help reduce social isolation, but issues exist regarding older adults’ access, feasibility, and motivation to use various forms of mobility and technology. This qualitative study explores how a diverse group of low-income, urban-living older adults use mobility and technology for social participation. We conducted six focus groups ( N = 48), two each in English, Spanish, and Korean at a Los Angeles senior center. Three major t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…In the field of education, this trend was more pronounced among older females who reside in rural areas and it was more pronounced among older males living in urban areas in terms of income. The finding is similar to the research by Gallo HB et al which established a positive correlation between income and ability to participate in social activities [ 48 ]. One possible explanation is that the older adults in China’s rural areas have limited access to education and income due to the country’s economic and educational constraints.…”
Section: Discussionsupporting
confidence: 91%
“…In the field of education, this trend was more pronounced among older females who reside in rural areas and it was more pronounced among older males living in urban areas in terms of income. The finding is similar to the research by Gallo HB et al which established a positive correlation between income and ability to participate in social activities [ 48 ]. One possible explanation is that the older adults in China’s rural areas have limited access to education and income due to the country’s economic and educational constraints.…”
Section: Discussionsupporting
confidence: 91%
“…Perceived participation on the other hand declined over time for all test persons, an effect that we attribute to the contact restriction measures during the COV-ID-19 pandemic. The analyses showed that participation was negatively influenced by the pandemic impacts on QoL as well as chronological age and economic situation, which is in line with previous research (Cruice, Worrall, & Hickson, 2005;Curvers, Pavlova, Hajema, Groot, & Angeli, 2018;Gallo, Marshall, Levy-Storms, Wilber, & Loukaitou-Sideris, 2022). The significant effects for the ATQoL measures can be classified as mostly low, the interaction effect sizes for all three measurement points were higher due to the consideration of multiple measurements (see Equation 1).…”
Section: Discussionsupporting
confidence: 87%
“…In focus group research from Senior Centers in Los Angeles, Gallo et al (2022) found older adults said that the crosswalk signals were not long enough for them to safely cross the street. Some of the focus group participants expressed distrust of the ride-hailing companies such as Uber/Lyft which further limited their mobility.…”
Section: Discussionmentioning
confidence: 99%